Jazz Age Barcelona - Davidson, Robert A. (Studies in book and print culture., 2009)
Jazz Age Barcelona focuses the lenses of cultural studies and urban studies on the avant-garde character of the city during the cosmopolitan Jazz Age, delving into the cultural forces that flourished in Europe between the late 1910s and early 1930s.